Air-stable sulfide solid electrolyte and preparation method thereof

By wrapping a 5-30nm-thick hydrophobic layer on the surface of the sulfide particles, the air stability problem of sulfide solid electrolyte is solved, and high ionic conductivity and suitable for mass-produced solid-state battery applications are achieved.

CN120280536AActive Publication Date: 2025-07-08GUOLIAN CORE MATERIALS (BEIJING) TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510234752.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-07-08
Estimated Expiration
2045-02-28

AI Technical Summary

Technical Problem

The air stability of existing sulfide solid electrolytes is poor, resulting in material failure and reduced ionic conductivity, limiting their large-scale production applications.

Method used

A hydrophobic layer with a thickness of 5 to 30 nm is wrapped on the surface of the sulfide particles. A long-chain hydrophobic polymer such as polytrifluoropropylmethylsiloxane is used to prepare air-stable solid electrolytes by mixing and drying.

Benefits of technology

It improves the air stability and ionic conductivity of sulfide solid electrolytes, is suitable for electrolytes of various particle sizes and morphology, is suitable for mass production, and improves the performance of all-solid state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005292451190000131
    Figure BDA0005292451190000131
  • Figure BDA0005292451190000141
    Figure BDA0005292451190000141
  • Figure BDA0005292451190000142
    Figure BDA0005292451190000142
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and particularly discloses an air-stable solid electrolyte. The solid electrolyte comprises a core and a hydrophobic layer wrapping the surface of the core, the core comprises sulfide particles, and the thickness of the hydrophobic layer is 5-30 nm. According to the solid-state electrolyte provided by the embodiment of the invention, the surface is coated with the hydrophobic layer with low surface activity, the air stability is high, and a solid-state battery with excellent battery performance can be prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of all-solid-state lithium-ion batteries, and more specifically, to air-stable sulfide solid electrolytes and their preparation methods. Even more specifically, it relates to a solid-state battery and an electronic device. Background Art

[0002] With the wider application of lithium batteries in life and the large-scale popularization of new energy vehicles, it is extremely urgent to improve the safety and energy density of lithium batteries. Traditional organic electrolytes are flammable, explosive, and prone to leakage, posing a huge safety hazard to lithium batteries. Replacing organic electrolytes with solid electrolytes is expected to fundamentally solve the battery safety hazard. Among various solid electrolytes, sulfide electrolytes are considered the most promising solid electrolyte materials due to their excellent mechanical ductility and high ionic conductivity.

[0003] However, the biggest drawback of sulfide solid electrolytes is their poor air stability. They will decompose with water to generate hydrogen sulfide gas, resulting in material failure, or the ionic conductivity will decrease due to environmental influence during long-term storage. Therefore, they are greatly affected by environmental conditions during preparation, use, and storage, which also limits their large-scale production and application and has become a key technical problem restricting the development of this field.

[0004] Therefore, there is an urgent need to develop air-stable sulfide solid electrolytes to improve the performance of solid-state batteries. Summary of the Invention

[0005] The present application aims to solve at least one of the technical problems existing in the prior art to some extent. For this purpose, the present application provides a sulfide solid electrolyte.

[0006] In a first aspect of the present application, a solid electrolyte is proposed. According to an embodiment of the present application, the solid electrolyte includes a core and a hydrophobic layer wrapped on the surface of the core. The core includes sulfide particles, and the thickness of the hydrophobic layer is 5 - 30 nm. According to the solid electrolyte of the embodiment of the present application, the surface is wrapped with a hydrophobic layer having low surface activity, with strong air stability, and can prepare a solid-state battery with excellent battery performance.

[0007] In some embodiments, the thickness of the hydrophobic layer is 8 - 20 nm.

[0008] In some embodiments, the hydrophobic layer includes a long-chain hydrophobic polymer.

[0009] In some embodiments, the long-chain hydrophobic polymer is selected from at least one of polytrifluoropropylmethylsiloxane, polydimethylsiloxane, polyacrylic acid, 1H,1H,2H,2H-perfluorodecyltriethoxysilane, methyl cellulose, ethyl cellulose, hydroxyethyl methacrylate, dodecyl methacrylate, fluorine-containing alkyl acrylate and silane-containing methyl acrylate.

[0010] In some embodiments, the long-chain hydrophobic polymer includes at least one functional group of -F-, -CF-, -Si-O-Si-, -Si-C-, -CO-, -Si-O-, and -C-Si-O-.

[0011] In some embodiments, the long-chain hydrophobic polymer includes at least one functional group of -F-, -CF-, -Si-O-Si, and -C-Si-O-.

[0012] In some embodiments, the sulfide particles are selected from Li2SiS3, Li2SnS3, Li3PS4, Li 5.5 PS 4.5 Cl 1.5 , Li 5.5 PS 4.5 Cl 0.8 Br 0.7 、Li7PS6、Li7P3S 11 、Li6PS5Cl、Li6PS5Br、Li 10 GeP2S 12 and Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 At least one of .

[0013] In some embodiments, the particle size distribution of the sulfide particles is 50 0.2μm~30μm.

[0014] In some embodiments, the ionic conductivity retention rate of the sulfide solid electrolyte is ≥ 90%.

[0015] In some embodiments, the ionic conductivity retention rate of the sulfide solid electrolyte is ≥ 95%.

[0016] The second aspect of the present application provides a method for preparing the solid electrolyte described in the first aspect of the present application. According to an embodiment of the present application, the method includes: mixing a solid electrolyte core material with a solid electrolyte hydrophobic layer material to obtain the solid electrolyte, the solid electrolyte including the core and a hydrophobic layer wrapped on the surface of the core, the core including sulfide particles, and the thickness of the hydrophobic layer being 5 - 30 nm. According to the method of the embodiment of the present application, a solid electrolyte with strong air stability can be prepared. According to the method of the embodiment of the present application, it can be applied to sulfide solid electrolytes with various particle sizes and various morphologies, and there is no need for expensive equipment and cumbersome processes, and it can be extended to mass production applications. Applying the prepared sulfide solid electrolyte to a solid-state battery can prepare a solid-state battery with excellent battery performance, which can meet the use requirements of high-energy-density all-solid-state batteries, and has good application prospects in all aspects.

[0017] In some embodiments, the solid electrolyte hydrophobic layer material includes a long-chain hydrophobic polymer.

[0018] In some embodiments, the mixing process includes: performing a first mixing process on the solid electrolyte hydrophobic layer material and a first solvent; performing a second mixing process on the product of the first mixing process and a second solvent; and performing a third mixing process on the product of the second mixing process and the solid electrolyte core material.

[0019] In some embodiments, the first solvent is selected from at least one of hexafluoroisopropanol, 1-bromopentane, polyethylene glycol dimethyl ether, and trifluoroacetic acid.

[0020] In some embodiments, the second solvent is selected from at least one of n-hexane, n-heptane, n-decane, n-butyl ether, anhydrous xylene, toluene, anisole, dibromomethane, and butyl butyrate.

[0021] In some embodiments, the first mixing process is carried out at a rotation speed of 500 - 700 r / min and a temperature of 40 - 80 °C for 5 - 15 h.

[0022] In some embodiments, the mass ratio of the solid electrolyte hydrophobic layer material to the first solvent is (0.1 - 3):(0.5 - 20).

[0023] In some embodiments, the second mixing process is carried out at a rotation speed of 300 - 1000 r / min and a temperature of 25 - 60 °C for 0.5 - 10 h.

[0024] In some embodiments, the mass ratio of the product of the first mixing process to the second solvent is (0.5 - 3):(1 - 5).

[0025] In some embodiments, the third mixing treatment is carried out for 0.5 - 10 h under the conditions of a rotation speed of 300 - 500 r / min and a temperature of 25 - 60 °C.

[0026] In some embodiments, the mass ratio of the solid electrolyte core material to the second mixing treatment product is (0.5 - 3):(1 - 10).

[0027] In some embodiments, after the third mixing treatment, it further includes drying the third mixing treatment product.

[0028] In some embodiments, the drying treatment is carried out for 2 - 20 h under the conditions of a temperature of 60 - 200 °C and an oven atmosphere of vacuum or inert gas.

[0029] The third aspect of the present application proposes the application of the solid electrolyte described in the first aspect of the present application or the solid electrolyte prepared by the method described in the second aspect of the present application in a all - solid - state lithium battery.

[0030] The fourth aspect of the present application proposes a solid - state battery. According to the embodiments of the present application, the solid - state battery includes a positive electrode, a negative electrode, and the solid electrolyte described in the first aspect of the present application or the solid electrolyte prepared by the method described in the second aspect of the present application.

[0031] The fifth aspect of the present application proposes an electronic device. According to the embodiments of the present application, the electronic device includes the solid - state battery described in the fourth aspect of the present application.

[0032] The additional aspects and advantages of the present application will be partially given in the following description, partially become obvious from the following description, or be understood through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The above - mentioned and / or additional aspects and advantages of the present application will become obvious and easy to understand from the description of the embodiments in conjunction with the following drawings, where:

[0034] Figure 1 It is the XRD diffraction pattern of the sulfide solid electrolyte material obtained in Example 1 of the present application.

[0035] Figure 2 It is the comparison chart of the initial charge - discharge specific capacity performance of the all - solid - state lithium battery assembled with the sulfide solid electrolyte materials obtained in Example 1 and Comparative Example 1 of the present application.

[0036] Figure 3 It is the comparison chart of the rate performance of the all - solid - state lithium battery assembled with the sulfide solid electrolyte materials obtained in Example 1 and Comparative Example 1 of the present application.

[0037] Figure 4This is a comparative graph of the cycle performance of all-solid-state lithium batteries assembled with the sulfide solid electrolyte material obtained in Example 1 of this application. Detailed implementation manners

[0038] The embodiments of the present application will be described in detail below. The examples of the embodiments are shown in the drawings, but there may be cases where unnecessary details are omitted. For example, there may be cases where the detailed description of well-known matters is omitted and the repeated description of actually identical structures is omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter recited in the claims.

[0039] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by those skilled in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise stated, the numerical values of the various parameters mentioned in this application can be measured by various commonly used measurement methods in the art (for example, they can be tested according to the methods given in the embodiments of this application).

[0040] The terms "including" and "having" and any variations thereof in the description and claims of this application are open expressions, that is, they include the content specified in this application, but do not exclude other aspects.

[0041] In the description of this application, it should be understood that the orientation or positional relationship indicated by terms such as "width" and "thickness" is based on the orientation or positional relationship shown in the drawings, and is only for the convenience of describing this application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation to this application.

[0042] In the description of this application, the terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly specifying the quantity of the indicated technical features. The "first feature" and "second feature" may include one or more of such features.

[0043] In the description of the present application, it should be understood that the orientation or positional relationship indicated by the terms "center", "longitudinal", "transverse", "length", "width", "thickness", "upper", "lower", "front", "rear", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. is based on the orientation or positional relationship shown in the drawings, and is only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be construed as a limitation to the present application.

[0044] In the description of the present application, unless otherwise clearly specified and defined, the first feature being "on" or "under" the second feature may be that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, the first feature being "above", "over" and "on top of" the second feature may be that the first feature is directly above or obliquely above the second feature, or merely indicates that the first feature has a higher horizontal height than the second feature. The first feature being "under", "beneath" and "underneath" the second feature may be that the first feature is directly below or obliquely below the second feature, or merely indicates that the first feature has a lower horizontal height than the second feature.

[0045] In the description of the present application, the meaning of "a plurality of" is two or more.

[0046] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, and any one of the cases of A and B, where A and B are only used for illustration and may be any technical features connected by "and / or" in the present application.

[0047] If there is no special instruction, all the embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0048] The prior art develops air-stable sulfide solid electrolytes by using the method of element doping. The limitation of this method is that the introduction of doping elements will lead to a decrease in the ionic conductivity of the electrolyte material, and some doping elements are highly toxic (such as arsenic As), which will affect the health of operators. In addition to element doping, there is also a modification method of coating the surface of the electrolyte. However, the preparation process of this method is relatively cumbersome and requires high-temperature sintering or atomic layer deposition technology (ALD), which increases energy consumption or requires expensive equipment and is not conducive to large-scale production applications.

[0049] Based on this, a first aspect of the present application proposes a solid electrolyte. According to an embodiment of the present application, the solid electrolyte includes a core and a hydrophobic layer wrapped on the surface of the core. The core includes sulfide particles, and the thickness of the hydrophobic layer is 5 to 30 nm, for example, it can be 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, 21 nm, 22 nm, 23 nm, 24 nm, 25 nm, 26 nm, 27 nm, 28 nm, 29 nm, 30 nm, and range values between them such as 6 to 30 nm, 7 to 30 nm. For the solid electrolyte according to the embodiment of the present application, the surface is wrapped with a hydrophobic layer having low surface activity, with strong air stability, and can be used to prepare a solid-state battery with excellent battery performance. A moderate thickness of the hydrophobic layer is beneficial for preparing the solid electrolyte. If the thickness of the hydrophobic layer is too thick, the ionic conductivity will be relatively low. If the thickness of the hydrophobic layer is too thin, the coating will be uneven and cannot play a role in protecting the solid electrolyte.

[0050] According to an embodiment of the present application, the thickness of the hydrophobic layer is 8 to 20 nm.

[0051] According to an embodiment of the present application, the hydrophobic layer includes a long-chain hydrophobic polymer.

[0052] According to an embodiment of the present application, the long-chain hydrophobic polymer is selected from at least one of poly(trifluoropropylmethylsiloxane) (PTFPMS), polydimethylsiloxane (PDMS), polyacrylic acid (PAA), 1H,1H,2H,2H-perfluorodecyltriethoxysilane (PFDTES), methylcellulose, ethylcellulose, 2-hydroxyethyl methacrylate, dodecyl methacrylate, fluoroalkyl acrylate, and silane group-containing methacrylate.

[0053] According to an embodiment of the present application, the long-chain hydrophobic polymer includes at least one functional group such as -F-, -C-F-, -Si-O-Si-, -Si-C-, -C-O-, -Si-O-, and -C-Si-O-. The long-chain segment is obtained through a polycondensation reaction between polymers.

[0054] According to an embodiment of the present application, the long-chain hydrophobic polymer includes at least one functional group such as -F-, -C-F-, -Si-O-Si, and -C-Si-O-.

[0055] According to an embodiment of the present application, the sulfide particles are selected from Li2SiS3, Li2SnS3, Li3PS4, Li 5.5 PS 4.5 Cl 1.5 、Li 5.5 PS 4.5Cl 0.8 Br 0.7 、Li7PS6, Li7P3S 11 、Li6PS5Cl, Li6PS5Br, Li 10 GeP2S 12 and Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 at least one of

[0056] According to an embodiment of the present application, the particle size distribution D of the sulfide particles 50 is 0.2 μm to 30 μm, and for example, it can be 0.2 μm, 1 μm, 3 μm, 5 μm, 7 μm, 9 μm, 11 μm, 13 μm, 15 μm, 17 μm, 19 μm, 21 μm, 23 μm, 25 μm, 27 μm, 29 μm, 30 μm or the range values between the two, such as 1 μm to 30 μm, 3 μm to 30 μm.

[0057] According to an embodiment of the present application, the solid electrolyte is left standing for 24 h at a dew point of -10°C.

[0058] According to an embodiment of the present application, the ion conductivity retention rate of the solid electrolyte is ≥ 90%. Here, it should be explained that the solid electrolyte is exposed to a humid environment, left standing in this environment for a period of time, and the ion conductivity before and after standing is measured. The ion conductivity retention rate refers to the ratio of the ion conductivity after exposure to the ion conductivity before exposure.

[0059] According to an embodiment of the present application, the ion conductivity retention rate of the solid electrolyte is ≥ 95%.

[0060] A second aspect of the present application provides a method for preparing the solid electrolyte described in the first aspect of the present application. According to an embodiment of the present application, the method includes: mixing the core material of the solid electrolyte with the hydrophobic layer material of the solid electrolyte to obtain the solid electrolyte, the solid electrolyte includes the core and the hydrophobic layer wrapped on the surface of the core, the core includes sulfide particles, and the thickness of the hydrophobic layer is 5 - 30 nm. The method according to the embodiment of the present application can prepare a solid electrolyte with strong air stability.

[0061] According to an embodiment of the present application, the hydrophobic layer material of the solid electrolyte includes long-chain hydrophobic polymers.

[0062] According to an embodiment of the present application, the long-chain hydrophobic polymer is selected from at least one of poly(trifluoropropylmethylsiloxane) (PTFPMS), polydimethylsiloxane (PDMS), polyacrylic acid (PAA), 1H,1H,2H,2H-perfluorodecyltriethoxysilane (PFDTES), methylcellulose, ethylcellulose, 2-hydroxyethyl methacrylate, dodecyl methacrylate, fluoroalkyl acrylate, and silylalkyl methacrylate.

[0063] According to an embodiment of the present application, the mixing treatment includes: performing a first mixing treatment on the solid electrolyte hydrophobic layer material and a first solvent; performing a second mixing treatment on the product of the first mixing treatment and a second solvent; and performing a third mixing treatment on the product of the second mixing treatment and the solid electrolyte core material.

[0064] According to an embodiment of the present application, the first solvent is selected from at least one of hexafluoroisopropanol, 1-bromopentane, polyethylene glycol dimethyl ether, and trifluoroacetic acid.

[0065] According to an embodiment of the present application, the second solvent is selected from at least one of n-hexane, n-heptane, n-decane, n-butyl ether, anhydrous xylene, toluene, anisole, dibromomethane, and butyl butyrate.

[0066] According to an embodiment of the present application, the first mixing treatment is carried out for 5 to 15 h under the conditions of a rotation speed of 500 to 700 r / min and a temperature of 40 to 80 °C.

[0067] According to an embodiment of the present application, the mass ratio of the solid electrolyte hydrophobic layer material to the first solvent is (0.1 to 3):(0.5 to 20).

[0068] According to an embodiment of the present application, the second mixing treatment is carried out for 0.5 to 10 h under the conditions of a rotation speed of 300 to 1000 r / min and a temperature of 25 to 60 °C.

[0069] According to an embodiment of the present application, the mass ratio of the product of the first mixing treatment to the second solvent is (0.5 to 3):(1 to 5).

[0070] According to an embodiment of the present application, the third mixing treatment is carried out for 0.5 to 10 h under the conditions of a rotation speed of 300 to 500 r / min and a temperature of 25 to 60 °C.

[0071] According to an embodiment of the present application, the mass ratio of the solid electrolyte core material to the product of the second mixing treatment is (0.5 to 3):(1 to 10).

[0072] According to an embodiment of the present application, the mass ratio of the solid electrolyte core material to the product of the second mixing treatment is (0.8 to 2):(2 to 6).

[0073] According to an embodiment of the present application, after the third mixing treatment, it further includes drying the third mixing treatment product.

[0074] According to an embodiment of the present application, the drying treatment is carried out for 2 - 20 h under the conditions that the temperature is 60 - 200 °C and the oven atmosphere is vacuum or inert gas.

[0075] According to an embodiment of the present application, the drying treatment is carried out for 5 - 15 h under the conditions that the temperature is 100 - 150 °C and the oven atmosphere is vacuum or inert gas.

[0076] The third aspect of the present application provides an application of the solid electrolyte described in the first aspect of the present application or the solid electrolyte prepared by the method described in the second aspect of the present application in a all - solid - state lithium battery.

[0077] The fourth aspect of the present application provides a solid - state battery. According to an embodiment of the present application, the solid - state battery includes a positive electrode, a negative electrode, and the solid electrolyte described in the first aspect of the present application or the solid electrolyte prepared by the method described in the second aspect of the present application. According to an embodiment of the present application, it should be noted that the "solid - state battery" includes all - solid - state batteries and batteries containing a certain proportion of liquid electrolyte, such as semi - solid - state batteries and quasi - solid - state batteries. Specifically, an all - solid - state battery does not contain any liquid electrolyte, and all electrolytes are solid. This type of battery usually has higher safety because the solid electrolyte is not flammable and can inhibit the growth of lithium dendrites, thereby reducing the risk of short - circuit. In addition, the energy density of an all - solid - state battery is usually higher because metallic lithium can be used as the negative electrode material, thus achieving a higher energy density. The all - solid - state battery has a long cycle life, a wide temperature adaptation range, and better mechanical strength and stability. A semi - solid - state battery contains a small amount of liquid electrolyte, usually the mass percentage of the liquid electrolyte is about 5 - 10%. While maintaining a high ion transport rate of a certain liquid battery, the semi - solid - state battery improves safety and is a transitional technology between traditional liquid lithium batteries and all - solid - state batteries. A quasi - solid - state battery refers to a battery in which the mass percentage of the liquid electrolyte is less than 5%. This type of battery has a higher content of solid electrolyte and less liquid electrolyte, and its safety is better than that of semi - solid - state batteries, but still not as good as that of all - solid - state batteries. For the solid - state battery according to the embodiment of the present application, the battery performance is improved.

[0078] The fifth aspect of the present application provides an electronic device. According to an embodiment of the present application, the electronic device includes the solid - state battery described in the fourth aspect of the present application.

[0079] Compared with the prior art, the advantages of the present application are as follows:

[0080] First, the air-stable solid electrolyte material provided by this application has a hydrophobic layer on its surface that is tightly wrapped around the solid electrolyte by bonding after in-situ polymerization, and the hydrophobic layer is not easily detached. This solid electrolyte not only has strong environmental adaptability but also high ionic conductivity; its coating method is applicable to solid electrolytes of various particle sizes and various morphologies. The composite electrode sheet and the ultra-thin solid electrolyte membrane prepared using this solid electrolyte have good surface flatness, and the assembled solid-state battery also has high discharge specific capacity, rate performance, and cycle stability.

[0081] Secondly, the preparation method of the air-stable solid electrolyte material provided by this application does not require expensive equipment, and the steps are simple, easy to implement, and can be scaled up for batch production applications. That is, by controlling the mass ratio, drying temperature ratio, and related parameters among the polymer, the first solvent, the second solvent, and the solid electrolyte, a hydrophobic coating with a controllable thickness on the surface of the solid electrolyte can be obtained, improving the environmental adaptability of the solid electrolyte, and having good prospects for practical industrial applications.

[0082] Finally, the preparation method provided by this application is applicable to solid electrolytes with small particle sizes. The obtained nano-scale air-stable solid electrolyte material is assembled into an all-solid-state lithium battery. Due to the improved air stability of the small-particle-size solid electrolyte, the all-solid-state battery has high discharge specific capacity and rate performance.

[0083] This application can improve the deficiencies of the solid electrolyte materials of existing all-solid-state lithium batteries, enhance air stability, and the preparation method has universality, enabling the solid electrolyte to be better applied to all-solid-state lithium batteries. At the same time, it also has good prospects for industrial applications.

[0084] The solutions of this application will be explained below in conjunction with examples. Those skilled in the art will understand that the following examples are only used to illustrate this application and should not be regarded as limiting the scope of this application. For those not specified in the examples regarding specific techniques or conditions, they shall be carried out according to the techniques or conditions described in the literature in this field or according to the product specifications. For reagents or instruments not specified for the manufacturer, they are all conventional products that can be obtained through commercial purchase.

[0085] Example 1

[0086] This example provides a solid electrolyte and its preparation method. Among them, the solid electrolyte contains sulfide particles Li 5.5 PS 4.5 Cl 1.5 The particle size distribution D 50 of the sulfide particles is 680 nm, the ionic conductivity σ is 7.42 mS cm -1 , and after standing at a dew point of -10 °C for 24 h, the ionic conductivity retention rate is 95%, and the thickness of the hydrophobic layer is 10 nm. The specific preparation process includes the following steps:

[0087] The polymer is PTFPMS, the first solvent is 1-bromopentane, and the second solvent is n-heptane. First, PTFPMS and 1-bromopentane are subjected to a first mixing treatment at a mass ratio of 1:5, a rotation speed of 600 r / min, and a temperature of 50 °C for 10 h to obtain a first mixing treatment product. Then, the first mixing treatment product and the second solvent n-heptane are subjected to a second mixing treatment at a mass ratio of 0.5:3, a rotation speed of 400 r / min, and a temperature of 40 °C for 5 h to obtain a second mixing treatment product. The second mixing treatment product is mixed with the Li 5.5 PS 4.5 Cl 1.5 at a mass ratio of 0.5:2, and a third mixing treatment is carried out at a rotation speed of 400 r / min and a temperature of 40 °C for 2 h to obtain a third mixing treatment product. The final third mixing treatment product is vacuum dried at 120 °C for 10 h to obtain a finally air-stable solid electrolyte.

[0088] Example 2

[0089] This example provides a solid electrolyte and a preparation method thereof. Among them, the solid electrolyte contains sulfide particles Li 10 GeP2S 12 , the particle size distribution D 50 of the sulfide particles is 620 nm, the ionic conductivity σ is 6.86 mS cm -1 , after standing for 24 h at a dew point of -10 °C, the retention rate of the ionic conductivity is 92%, and the thickness of the hydrophobic layer is 15 nm. The specific preparation process includes the following steps:

[0090] The polymer is PDMS, the first solvent is polyethylene glycol dimethyl ether, and the second solvent is n-butyl ether. First, PDMS and polyethylene glycol dimethyl ether are subjected to a first mixing treatment at a mass ratio of 1:8, a rotation speed of 650 r / min, and a temperature of 60 °C for 12 h to obtain a first mixing treatment product. Then, the first mixing treatment product and the second solvent n-butyl ether are subjected to a second mixing treatment at a mass ratio of 1:5, a rotation speed of 500 r / min, and a temperature of 30 °C for 8 h to obtain a second mixing treatment product. The second mixing treatment product is mixed with the Li 10 GeP2S 12 at a mass ratio of 1:3, and a third mixing treatment is carried out at a rotation speed of 300 r / min and a temperature of 45 °C for 5 h to obtain a third mixing treatment product. The final third mixing treatment product is vacuum dried at 130 °C for 12 h to obtain a finally air-stable solid electrolyte.

[0091] Example 3

[0092] This embodiment provides a solid electrolyte and a preparation method thereof. Among them, the solid electrolyte contains sulfide particles Li6PS5Cl, and the particle size distribution D of the sulfide particles 50 is 3 μm, the ionic conductivity σ is 3.12 mS cm -1 , after standing for 24 h at a dew point of -10 °C, the retention rate of ionic conductivity is 93%, and the thickness of the hydrophobic layer is 12 nm. The specific preparation process includes the following steps:

[0093] The polymer is PAA, the first solvent is hexafluoroisopropanol, and the second solvent is toluene. First, PAA and hexafluoroisopropanol are subjected to a first mixing treatment at a mass ratio of 1:3, a rotation speed of 580 r / min, and a temperature of 55 °C for 15 h to obtain a first mixing treatment product. Then, the first mixing treatment product and the second solvent toluene are subjected to a second mixing treatment at a mass ratio of 1:4, a rotation speed of 500 r / min, and a temperature of 45 °C for 5 h to obtain a second mixing treatment product. The second mixing treatment product and the Li6PS5Cl are subjected to a third mixing treatment at a mass ratio of 2:3, a rotation speed of 450 r / min, and a temperature of 30 °C for 4 h to obtain a third mixing treatment product. The final third mixing treatment product is vacuum dried at 110 °C for 8 h to obtain a finally air-stable solid electrolyte.

[0094] Example 4

[0095] This embodiment provides a solid electrolyte and a preparation method thereof. Among them, the solid electrolyte contains sulfide particles Li7P3S 11 , and the particle size distribution D of the sulfide particles 50 is 5 μm, the ionic conductivity σ is 2.42 mS cm -1 , after standing for 24 h at a dew point of -10 °C, the retention rate of ionic conductivity is 91%, and the thickness of the hydrophobic layer is 10 nm. The specific preparation process includes the following steps:

[0096] The polymer is PFDTES, the first solvent is hexafluoroisopropanol, and the second solvent is butyl butyrate. First, PFDTES and hexafluoroisopropanol are subjected to a first mixing treatment at a mass ratio of 0.5:2, a rotation speed of 600 r / min, and a temperature of 50 °C for 13 h to obtain a first mixing treatment product. Then, the first mixing treatment product and the second solvent butyl butyrate are subjected to a second mixing treatment at a mass ratio of 1:5, a rotation speed of 500 r / min, and a temperature of 40 °C for 8 h to obtain a second mixing treatment product. The second mixing treatment product and the Li7P3S 11The third mixing treatment is carried out at a mass ratio of 2:5, a rotation speed of 500 r / min, and a temperature of 55 °C for 6 h to obtain the third mixing treatment product. The final third mixing treatment product is vacuum dried at 100 °C for 10 h to obtain the final air-stable solid electrolyte.

[0097] Example 5

[0098] This example provides a solid electrolyte and a preparation method thereof. Among them, the solid electrolyte contains sulfide particles Li 5.5 PS 4.5 Cl 0.8 Br 0.7 , the particle size distribution D of the sulfide particles 50 is 2 μm, the ionic conductivity σ is 8.42 mS cm -1 , after standing for 24 h at a dew point of -10 °C, the retention rate of the ionic conductivity is 94%, and the thickness of the hydrophobic layer is 8 nm. The specific preparation process includes the following steps:

[0099] The polymer is PTFPMS, the first solvent is hexafluoroisopropanol, and the second solvent is n-hexane. First, PTFPMS and hexafluoroisopropanol are subjected to the first mixing treatment at a mass ratio of 1:3, a rotation speed of 700 r / min, and a temperature of 60 °C for 10 h to obtain the first mixing treatment product. Then, the first mixing treatment product and the second solvent n-hexane are subjected to the second mixing treatment at a mass ratio of 1:3, a rotation speed of 500 r / min, and a temperature of 40 °C for 5 h to obtain the second mixing treatment product. The second mixing treatment product and the Li 5.5 PS 4.5 Cl 0.8 Br 0.7 are subjected to the third mixing treatment at a mass ratio of 1:3, a rotation speed of 350 r / min, and a temperature of 50 °C for 3 h to obtain the third mixing treatment product. The final third mixing treatment product is vacuum dried at 100 °C for 5 h to obtain the final air-stable solid electrolyte.

[0100] Example 6

[0101] The preparation is carried out by the same method as in Example 1, except that the polymer PTFPMS and the first solvent 1-bromopentane are mixed at a mass ratio of 3:0.5, and the other processes are the same as in Example 1.

[0102] Example 7

[0103] The preparation is carried out by the same method as in Example 1, except that the polymer PTFPMS and the first solvent 1-bromopentane are mixed at a mass ratio of 0.1:20, and the other processes are the same as in Example 1.

[0104] Example 8

[0105] It was prepared by the method of Example 1, except that the polymer PTFPMS and the first solvent 1-bromopentane were mixed at a mass ratio of 4:0.5, and the other processes were the same as those in Example 1.

[0106] Example 9

[0107] It was prepared by the method of Example 1, except that the polymer PTFPMS and the first solvent 1-bromopentane were mixed at a mass ratio of 0.1:21, and the other processes were the same as those in Example 1.

[0108] Example 10

[0109] It was prepared by the method of Example 1, except that the solid electrolyte core material and the second mixed treatment product were mixed at a mass ratio of 0.5:10, and the other processes were the same as those in Example 1.

[0110] Example 11

[0111] It was prepared by the method of Example 1, except that the solid electrolyte core material and the second mixed treatment product were mixed at a mass ratio of 3:1, and the other processes were the same as those in Example 1.

[0112] Example 12

[0113] It was prepared by the method of Example 1, except that the solid electrolyte core material and the second mixed treatment product were mixed at a mass ratio of 0.4:10, and the other processes were the same as those in Example 1.

[0114] Example 13

[0115] It was prepared by the method of Example 1, except that the solid electrolyte core material and the second mixed treatment product were mixed at a mass ratio of 4:1, and the other processes were the same as those in Example 1.

[0116] Example 14

[0117] It was prepared by the method of Example 1, except that the drying temperature was 200 °C, and the other processes were the same as those in Example 1.

[0118] Example 15

[0119] It was prepared by the method of Example 1, except that the drying temperature was 60 °C, and the other processes were the same as those in Example 1.

[0120] Example 16

[0121] It was prepared by the method of Example 1, except that the drying temperature was 210 °C, and the other processes were the same as those in Example 1.

[0122] Example 17

[0123] It was prepared by the method of Example 1, except that the drying temperature was 50 °C, and the other processes were the same as those in Example 1.

[0124] Example 18

[0125] It was prepared by the method of Example 1, except that the polymer was polydimethylsiloxane, and the other processes were the same as those in Example 1.

[0126] Example 19

[0127] It was prepared by the method of Example 1, except that the polymer was polyvinyl alcohol, and the other processes were the same as those in Example 1.

[0128] Example 20

[0129] It was prepared by the method of Example 1, except that the first solvent was polyethylene glycol dimethyl ether, and the other processes were the same as those in Example 1.

[0130] Example 21

[0131] It was prepared by the method of Example 1, except that the first solvent was tetrahydrofuran, and the other processes were the same as those in Example 1.

[0132] Example 22

[0133] It was prepared by the method of Example 1, except that the second solvent was n-hexane, and the other processes were the same as those in Example 1.

[0134] Example 23

[0135] It was prepared by the method of Example 1, except that the second solvent was dichloromethane, and the other processes were the same as those in Example 1.

[0136] Example 24

[0137] It was prepared by the method of Example 1, except that the thickness of the hydrophobic layer was 5 nm, and the other processes were the same as those in Example 1.

[0138] Example 25

[0139] It was prepared by the method of Example 1, except that the thickness of the hydrophobic layer was 30 nm, and the other processes were the same as those in Example 1.

[0140] Comparative Example 1

[0141] The experimental process of this comparative example is basically the same as that of Example 1. The sulfide solid electrolyte material in Example 1 is used. The difference is that the polymer PTFPMS and the first solvent 1-bromopentane are not added, and the other processes are the same as those in Example 1.

[0142] Comparative Example 2

[0143] The experimental process of this comparative example is basically the same as that of Example 1. The difference is that the polymer PTFPMS is not added, and the other processes are the same as those in Example 1.

[0144] Comparative Example 3

[0145] The experimental process of this comparative example is basically the same as that of Example 1. The difference is that the thickness of the hydrophobic layer is 4 nm, and the other processes are the same as those in Example 1.

[0146] Comparative Example 4

[0147] The experimental process of this comparative example is basically the same as that of Example 1. The difference is that the thickness of the hydrophobic layer is 31 nm, and the other processes are the same as those in Example 1.

[0148] Test Example

[0149] XRD experiment: First, put the sulfide electrolyte powder into a customized mold, then stick the sealing tape to avoid contact with air, and finally put the prepared sample into the XRD tester for testing. The XRD diffraction pattern of the sulfide solid electrolyte material obtained in Example 1 is as Figure 1 shown.

[0150] Ionic conductivity test: Weigh 150 mg of the sulfide solid electrolyte materials in Examples 1 to 25 and Comparative Examples 1 to 4, place them in a mold with an inner diameter of 10 mm, press them with stainless steel current collector rods on the top and bottom, apply a pressure of 370 MPa for 5 min, and perform AC impedance testing using an electrochemical workstation at 25 °C. The amplitude of the alternating current is 15 mV, and the frequency range is 0.01 HZ to 1 MHz.

[0151] Wet air stability test of the solid electrolyte material: Perform wet air stability tests on the sulfide solid electrolytes in Examples 1 to 25 and Comparative Examples 1 to 4. Inside the glove box, weigh 300 mg of the solid electrolyte material and put it into a 5 mL open glass bottle. Then place the glass bottle in a reaction box with a specific humidity air flow, and let it stand at room temperature. The relative humidity of the wet air is 10% (equivalent to a dew point of about -10 °C), and the air flow rate is 100 mL / min. After 24 h, take samples for ion conductivity testing.

[0152] Assembly of Solid-State Lithium Batteries: Among them, the solid-state lithium battery is composed of a high-nickel cathode material, a lithium-indium alloy anode, and the sulfide solid electrolyte material prepared in Examples 1-25 or Comparative Examples 1-4 above. The specific assembly process is as follows: First, 100 mg of the sulfide solid electrolyte is loaded into a Φ10 mm mold and pressed into an intermediate layer sheet under a pressure of 200 MPa; then, 10 mg of the composite cathode material (composed of 7 mg of the high-nickel cathode material and 3 mg of the sulfide solid electrolyte) is added to one end of the intermediate layer sheet and pressed into shape under a pressure of 200 MPa; finally, a certain amount of the lithium-indium alloy anode is added to the other end of the intermediate layer sheet and assembled into a all-solid-state lithium battery under a pressure of 240 MPa.

[0153] Testing of Solid-State Lithium Batteries: The test temperature is 25 °C, and the voltage range is 2.6 - 4.4 V vs. Li + / Li. The first-cycle charge-discharge capacity and Coulomb efficiency of the full cell are tested at a current density of 0.1 C (1 C = 200 mA g -1 ); the rate performance is tested at different current densities of 0.2 C, 0.5 C, 0.8 C, 1 C, 2 C, and 3 C; the long-cycle performance is tested at a current density of 1 C, and the number of cycles when the capacity retention decays to 80% is recorded. The comparison chart of the first charge-discharge specific capacity performance of the all-solid-state lithium batteries assembled with the sulfide solid electrolyte materials obtained in Example 1 and Comparative Example 1 is as Figure 2 shown. The comparison chart of the rate performance of the all-solid-state lithium batteries assembled with the sulfide solid electrolyte materials obtained in Example 1 and Comparative Example 1 is as Figure 3 shown. The comparison chart of the cycle performance of the all-solid-state lithium battery assembled with the sulfide solid electrolyte material obtained in Example 1 is as Figure 4 shown.

[0154] Table 1: Characteristics of Sulfide Solid Electrolyte Materials in Examples 1-25 and Comparative Examples 1-4

[0155]

[0156]

[0157] Table 2: Performance Data of All-Solid-State Lithium Batteries in Examples 1-25 and Comparative Examples 1-4

[0158]

[0159]

[0160] From the data analysis of Table 1 and Table 2, it can be seen that the air-stable sulfide solid electrolyte material of the present application has high ionic conductivity and wet air stability. The preparation method has universality. The all-solid-state lithium battery composed of the air-stable sulfide solid electrolyte material of the present application has good discharge specific capacity, high rate performance and stable long-cycle performance. This is due to the fact that the sulfide electrolyte of the present invention is coated with a hydrophobic layer with low surface activity, and the hydrophobic layer is tightly wrapped on the sulfide solid electrolyte by bonding after in-situ polymerization, having a hydrophobic effect.

[0161] By comparing Example 1 with Comparative Example 1 and Comparative Example 2, it is found that the interface treatment significantly improves the wet air stability of the sulfide solid electrolyte, and at the same time, the comprehensive performance of the all-solid-state lithium battery is significantly improved. This fully shows that improving the environmental adaptability in the all-solid-state battery is crucial for the performance of the entire battery.

[0162] By comparing Example 1, Example 24, Example 25 with Comparative Example 3 and Comparative Example 4, it can be obtained that the retention rate of the ionic conductivity of the solid electrolyte prepared with a hydrophobic layer of 5nm - 30nm increases, and the number of cycles for the (1C) capacity retention rate of the prepared solid-state battery to decay to 80% increases.

[0163] By comparing Example 1, Example 2, Example 3, Example 4 and Example 5, it can be obtained that although the surface coating materials of the sulfide solid electrolyte are different, and the process parameters in the preparation process are different, the material characteristics of the obtained sulfide solid electrolyte and the electrochemical performance of the assembled all-solid-state lithium battery also have slight differences. This shows that while obtaining an air-stable sulfide electrolyte, by adjusting the preparation parameters and changing the coating material on the surface of the sulfide solid electrolyte, the performance of the all-solid-state lithium battery can be optimized.

[0164] By comparing Example 1, Example 6, Example 7 with Example 8 and Example 9, it can be obtained that the retention rate of the ionic conductivity of the solid electrolyte prepared with the mass ratio of the polymer to 1-bromopentane in the range of (0.1 - 3):(0.5 - 20) increases, and the number of cycles for the (1C) capacity retention rate of the prepared solid-state battery to decay to 80% increases.

[0165] By comparing Example 1, Example 10, Example 11 with Example 12 and Example 13, it can be obtained that the retention rate of the ionic conductivity of the solid electrolyte prepared with the mass ratio of the core material of the solid electrolyte to the second mixed treatment product in the range of (0.5 - 3):(1 - 10) increases, and the number of cycles for the (1C) capacity retention rate of the prepared solid-state battery to decay to 80% increases.

[0166] Comparing Example 1, Example 14, Example 15 with Example 16 and Example 17, it can be obtained that the retention rate of the ionic conductivity of the solid electrolyte prepared within the range of 60 to 200 °C of the drying temperature is increased, and the number of cycles for the (1C) capacity retention rate of the prepared solid-state battery to decay to 80% is increased.

[0167] Comparing Example 1, Example 18 with Example 19, it can be obtained that the retention rate of the ionic conductivity of the solid electrolyte prepared with polytetrafluoropropylmethylsiloxane or polydimethylsiloxane as the polymer is higher than that prepared with polyvinyl alcohol, and the number of cycles for the (1C) capacity retention rate of the prepared solid-state battery to decay to 80% is increased.

[0168] Comparing Example 1, Example 20 with Example 21, it can be obtained that the retention rate of the ionic conductivity of the solid electrolyte prepared with dimethoxydiethyleneglycol or 1-bromopentane as the first solvent is higher than that prepared with tetrahydrofuran, and the number of cycles for the (1C) capacity retention rate of the prepared solid-state battery to decay to 80% is increased.

[0169] Comparing Example 1, Example 22 with Example 23, it can be obtained that the retention rate of the ionic conductivity of the solid electrolyte prepared with n-hexane or n-heptane as the second solvent is higher than that prepared with dichloromethane, and the number of cycles for the (1C) capacity retention rate of the prepared solid-state battery to decay to 80% is increased.

[0170] In the description of this specification, the descriptions with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples", etc. mean that the specific features, structures, materials, or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described can be combined in a suitable manner in any one or more embodiments or examples. In addition, without contradiction, those skilled in the art can combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples.

[0171] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and should not be construed as limiting the present application. Those of ordinary skill in the art can make changes, modifications, substitutions, and variations to the above embodiments within the scope of the present application.

Claims

1. A solid electrolyte, characterized in that, The solid electrolyte includes a core and a hydrophobic layer wrapped on the surface of the core. The core includes sulfide particles, and the thickness of the hydrophobic layer is 5 to 30 nm.

2. The solid electrolyte according to claim 1, characterized in that, The thickness of the hydrophobic layer is 8 to 20 nm.

3. The solid electrolyte according to claim 1, characterized in that, The hydrophobic layer includes a long-chain hydrophobic polymer; Optionally, the long-chain hydrophobic polymer is selected from at least one of poly(trifluoropropylmethylsiloxane), polydimethylsiloxane, polyacrylic acid, 1H,1H,2H,2H-perfluorodecyltriethoxysilane, methylcellulose, ethylcellulose, 2-hydroxyethyl methacrylate, dodecyl methacrylate, fluoroalkyl acrylate, and silyl group-containing methacrylate; Optionally, the long-chain hydrophobic polymer includes at least one functional group of -F-, -C-F-, -Si-O-Si-, -Si-C-, -C-O-, -Si-O-, and -C-Si-O-; Optionally, the long-chain hydrophobic polymer includes at least one functional group of -F-, -C-F-, -Si-O-Si, and -C-Si-O-; 4. The solid electrolyte according to claim 1, characterized in that, The sulfide particles are selected from at least one of Li2SiS3, Li2SnS3, Li3PS4, Li 5.5 PS 4.5 Cl 1.5 、Li 5.5 PS 4.5 Cl 0.8 Br 0.7 、Li7PS6, Li7P3S 11 、Li6PS5Cl, Li6PS5Br, Li 10 GeP2S 12 and Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 among others.

5. The solid electrolyte according to claim 1, characterized in that, The particle size distribution D of the sulfide particles 50 is 0.2 μm to 30 μm.

6. A method for preparing the solid electrolyte according to any one of claims 1 to 5, characterized in that, Including: Mixing a solid electrolyte core material and a solid electrolyte hydrophobic layer material to obtain the solid electrolyte. The solid electrolyte includes the core and a hydrophobic layer wrapped on the surface of the core. The core includes sulfide particles, and the thickness of the hydrophobic layer is 5 to 30 nm.

7. The method according to claim 6, characterized in that The solid electrolyte hydrophobic layer material includes a long-chain hydrophobic polymer.

8. The method according to claim 6, wherein The mixing process includes: Performing a first mixing process on the solid electrolyte hydrophobic layer material and a first solvent; Performing a second mixing process on the first mixing product and a second solvent; Performing a third mixing process on the second mixing product and the solid electrolyte core material; Optionally, the first solvent is selected from at least one of hexafluoroisopropanol, 1-bromopentane, polyethylene glycol dimethyl ether, and trifluoroacetic acid; Optionally, the second solvent is selected from at least one of n-hexane, n-heptane, n-decane, n-butyl ether, anhydrous xylene, toluene, anisole, dibromomethane, and butyl butyrate; 9. According to the method of claim 8, wherein The first mixing process is carried out at a rotation speed of 500 to 700 r / min and a temperature of 40 to 80 °C for 5 to 15 h; And / or, the mass ratio of the solid electrolyte hydrophobic layer material to the first solvent is (0.1 to 3):(0.5 to 20); And / or, the second mixing process is carried out at a rotation speed of 300 to 1000 r / min and a temperature of 25 to 60 °C for 0.5 to 10 h; And / or, the mass ratio of the first mixing product to the second solvent is (0.5 to 3):(1 to 5); And / or, the third mixing process is carried out at a rotation speed of 300 to 500 r / min and a temperature of 25 to 60 °C for 0.5 to 10 h; And / or, the mass ratio of the solid electrolyte core material to the second mixing product is (0.5 to 3):(1 to 10); And / or, after the third mixing process, further including drying the third mixing product; And / or, the drying treatment is carried out at a temperature of 60 to 200 °C for 2 to 20 h under the condition that the oven atmosphere is vacuum or inert gas.

10. Application of the solid electrolyte according to any one of claims 1 to 5 or the solid electrolyte prepared by the method according to any one of claims 6 to 9 in a all-solid-state lithium battery.

11. A solid-state battery, characterized in that, Comprising: A positive electrode, a negative electrode and the solid electrolyte according to any one of claims 1 to 5 or the solid electrolyte prepared by the method according to any one of claims 6 to 9.

12. An electronic device, characterized in that, Comprising: The solid-state battery according to claim 11.

Citation Information

Patent Citations

  • Solid state electrolyte layer, electrode active material layer, all solid state lithium battery, manufacturing method for solid state electrolyte layer, and manufacturing method for electrode active material layer

    CN102035021A

  • Porous polymer electrolyte supporting membrane material, preparation method thereof and application thereof

    CN102199846A

  • Super-hydrophobic material capable of conducting lithium ions as well as preparation method and application thereof

    CN112701345A

  • Modified lithium nitrogen halide solid electrolyte as well as preparation method and application thereof

    CN117712471A

  • Water-stable inorganic sulfide electrolyte, preparation method thereof and battery

    CN118040019A

Cited By

  • High-moisture-resistance sulfide solid electrolyte, preparation method thereof and all-solid-state battery

    CN122494863A